Nilai Pendidikan Agama Hindu dalam Teks Tutur Jatiswara - Ni Wayan Mira Apsari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Tutur is a type of traditional literary work in the form of prose, which contains religious, philosophical and life values. The speech that will be used as study material in this journal article is entitled Tutur Jatiswara. Jatiswara speech text is a spoken text that describes the advice of parents to their children. The problem statement in this journal article is (1). The structure of the Jatiswara speech text. (2). The educational value contained in the text said Jatiswara. The objectives contained in this journal article are divided into 2, namely general goals and specific goals. The general objective in this journal article is to develop and preserve traditional Balinese literature, especially literary works in the form of speech. The specific objectives in this journal article are (1) to find out the structure contained in Jatiswara's spoken text. (2) This is to determine the value of Hindu religious education in the Jatiswara speech text. The method used in writing this journal article is by using a review method from several sources or what is called the literature method.